Peroxiredoxin 6 protects irradiated cells from oxidative stress and shapes their senescence-associated cytokine landscape - Salovska, Barbora; Kondelova, Alexandra; Pimkova, Kristyna; Liblova, Zuzana; Pribyl, Miroslav; Fabrik, Ivo; Bartek, Jiri; Vajrychova, Marie; Hodny, Zdenek (Redox biology, 2022)
Cellular senescence is a complex stress response defined as an essentially irreversible cell cycle arrest mediated by the inhibition of cell cycle-specific cyclin dependent kinases. The imbalance in redox homeostasis and oxidative stress have been repeatedly observed as one of the hallmarks of the senescent phenotype. However, a large-scale study investigating protein oxidation and redox signaling in senescent cells in vitro has been lacking. Here we applied a proteome-wide analysis using SILAC-iodoTMT workflow to quantitatively estimate the level of protein sulfhydryl oxidation and proteome level changes in ionizing radiation-induced senescence (IRIS) in hTERT-RPE-1 cells. We observed that senescent cells mobilized the antioxidant system to buffer the increased oxidation stress. Among the antioxidant proteins with increased relative abundance in IRIS, a unique 1-Cys peroxiredoxin family member, peroxiredoxin 6 (PRDX6), was identified as an important contributor to protection against oxidative stress. PRDX6 silencing increased ROS production in senescent cells, decreased their resistance to oxidative stress-induced cell death, and impaired their viability. Subsequent SILAC-iodoTMT and secretome analysis after PRDX6 silencing showed the downregulation of PRDX6 in IRIS affected protein secretory pathways, decreased expression of extracellular matrix proteins, and led to unexpected attenuation of senescence-associated secretory phenotype (SASP). The latter was exemplified by decreased secretion of pro-inflammatory cytokine IL-6 which was also confirmed after treatment with an inhibitor of PRDX6 iPLA2 activity, MJ33. In conclusion, by combining different methodological approaches we discovered a novel role of PRDX6 in senescent cell viability and SASP development. Our results suggest PRDX6 could have a potential as a drug target for senolytic or senomodulatory therapy.
Keywords: Peroxiredoxin VI; peroxiredoxin VI; Cellular senescence; SILAC-iodoTMT; Oxidative Stress; cytokiny; Interleukin 6; Senescence-associated secretory phenotype; oxidace-redukce; stárnutí buněk; Cytokines; oxidační stres; Oxidation-Reduction; Cellular Senescence; Peroxiredoxin 6; Redox proteomics